Pragmatic Diversification in ASEAN: Strategic Responses to Trade War Ripple Effects in 2025 - Hengki Mangiring Parulian Simarmata; Poltak Pardamean Simarmata (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
This study explores how selected ASEAN countries Vietnam, Indonesia, and Thailand strategically diversified their trade partnerships in response to the global trade war ripple effects in 2025. Amid intensifying geopolitical tension, technological decoupling, and rising non-tariff trade barriers, these countries have adopted distinct strategies: Vietnam pursues export-led realignment, Indonesia promotes resource-based sovereignty, and Thailand engages in hybrid sectoral diplomacy. Through qualitative content analysis of trade policy documents and institutional reports, the study identifies a shared pattern of reduced dependence on traditional powers while highlighting the fragmented nature of ASEAN-wide coordination. The findings offer new insights into